2007
DOI: 10.4049/jimmunol.179.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Antioxidative Properties of Myeloid Dendritic Cells: Protection of T Cells and NK Cells from Oxygen Radical-Induced Inactivation and Apoptosis

Abstract: Dendritic cells (DCs) communicate with nonadaptive and adaptive lymphocytes on multiple levels. Efficient DC-lymphocyte interactions require that lymphocytes remain viable and functional also under conditions of oxidative stress, such as in microbial infection or in the malignant microenvironment. For this study, we exposed human T and NK cells to oxidants delivered either by autologous phagocytes or in the form of exogenous hydrogen peroxide. In accordance with earlier studies, these lymphocytes became dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…Because immature DCs were highly efficient in inducing thiol expression in T cells, it seems reasonable to assume that the capacity of DCs to induce thiol expression in T cells cannot be further enhanced by maturation. These data are in accordance with a previous study showing that immature and mature DCs confer a similar level of protection from oxygen radical-induced inactivation to coincubated lymphocytes (20).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Because immature DCs were highly efficient in inducing thiol expression in T cells, it seems reasonable to assume that the capacity of DCs to induce thiol expression in T cells cannot be further enhanced by maturation. These data are in accordance with a previous study showing that immature and mature DCs confer a similar level of protection from oxygen radical-induced inactivation to coincubated lymphocytes (20).…”
Section: Discussionsupporting
confidence: 83%
“…This study showed that DCs furnish effector T cells with cs-and ic-thiols during presentation of viral and bacterial Ags and that T cells with enhanced thiol expression consume ROS and escape oxidant-induced apoptosis. In accordance with previous studies (18,20), a slight, but significant, increase in thiol expression was observed on all T cells cocultured with DCs. However, using Ag-pulsed DCs and detection of Agspecific TCR/Vb regions or tetramer technology, we found that the DC-induced thiol expression was several-fold higher in T cells specific for the presented Ag.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Besides the involvement of redox-sensitive NF-kB and Nrf2 transcription factors in T cell activation [68,69] and additional evidence indicating the involvement of ROS in T cell activation and proliferation [70][71][72], very limited information is currently available on the regulatory and signaling mechanisms involved in ROS response. To generate specific responses, ROS need to interact with molecular sensors, likely to be cysteine residues located in regulatory elements.…”
Section: Discussionmentioning
confidence: 99%